2006
DOI: 10.4103/0973-3930.33180
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous manifestations of diabetes mellitus

Abstract: Hmsqnctbshnm Diabetes mellitus (DM) is a worldwide problem and the most common endocrine disorder. Its prevalence is increasing in the present scenario of a sedentary lifestyle in the general population. Abnormalities of insulin and elevated blood glucose level lead to metabolic, vascular, neurological and immunological abnormalities. Affected organs include the cardiovascular, renal and nervous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 7 publications
(10 reference statements)
2
1
0
1
Order By: Relevance
“…We found a high prevalence of cutaneous manifestation of T2DM. The prevalence was similar to that in India, Pakistan and Hong Kong which is between 58 to 67% [10,15,16]. Skin infection was the most common cutaneous manifestation of T2DM in our patients, followed by SDWSAD with diabetic dermopathy.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We found a high prevalence of cutaneous manifestation of T2DM. The prevalence was similar to that in India, Pakistan and Hong Kong which is between 58 to 67% [10,15,16]. Skin infection was the most common cutaneous manifestation of T2DM in our patients, followed by SDWSAD with diabetic dermopathy.…”
Section: Discussionsupporting
confidence: 84%
“…Skin infection was the most common cutaneous manifestation of T2DM in our patients, followed by SDWSAD with diabetic dermopathy. Infections and diabetic dermopa-thy are common cutaneous disorders associated with diabetes [8,15,16]. Diabetic foot and trophic ulcer were the most common manifestations of SMDC.…”
Section: Discussionmentioning
confidence: 99%
“…12 Infections increases the possibility of developing neurovascular and other systemic complications which can give rise to various dermatological manifestations. 13 In the present study, 116 (96.7%) were type 2 diabetes mellitus and 4 (3.3%) were type a diabetes. In a study by Nigam PK et al reported that 82.1% of subjects had type 2 diabetes.…”
Section: Discussionsupporting
confidence: 44%
“…La PDS inicia en áreas distales de las extremidades siguiendo un patrón en "guantes y medias" con síntomas como el adormecimiento, hormigueo, dolor lancinante y, en algunos casos, debilidad muscular. Puede preceder la aparición de lesiones cutáneas y acompañarse de hipohidrosis o anhidrosis (28) , cambios en la transpiración que generalmente afectan las extremidades inferiores, causan xerosis y fisuras en la piel, que favorece el ingreso de patógenos.…”
Section: Neuropatía Diabéticaunclassified